2015
DOI: 10.1088/0953-2048/28/9/095005
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-annealing effects on superconductivity in polycrystalline Fe1+xTe1−ySey

Abstract: Superconductivity in anti-PbO-type iron chalcogenides Fe1+xTe1−ySey (x = 0, 0.1, y = 0.1–0.4) depends on the amount (x) of interstitial iron atoms located between the FeTe1−ySey layers. Non-superconducting samples of nominal Fe1.1Te1−ySey convert to superconductors with critical temperatures up to 14 K after annealing at 300 °C in an oxygen atmosphere. The process is irreversible upon subsequent hydrogen annealing. Magnetic measurements are consistent with the formation of iron oxides, suggesting that oxygen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Therefore, it can be deduced that the superconductivity of final product is very sensitive to the stoichiometry [19,20] . Based on previous report, excess Fe can promote the superconducting phase formation, but it hinders the appearance of bulk superconductivity [21] . Therefore, it is necessary to remove the excess Fe after the formation of superconducting phase.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, it can be deduced that the superconductivity of final product is very sensitive to the stoichiometry [19,20] . Based on previous report, excess Fe can promote the superconducting phase formation, but it hinders the appearance of bulk superconductivity [21] . Therefore, it is necessary to remove the excess Fe after the formation of superconducting phase.…”
Section: Introductionmentioning
confidence: 88%
“…The heterogeneous reaction begins at the surface and probably causes inhomogeneous particle distribution, accompanied by FeTe 2 impurity formation. Thus, the anti-PbO-type phase obviously degrades if iron is extracted from the layers of FeTe 1-y Se y tetrahedra [16,17].…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…However, to our best knowledge, none of the studies performed in assistance of the hydrogen atmosphere reported systematic evolution of macroscopic superconducting parameters. Annealing of the Fe-Te-Se compound in an oxygen atmosphere at temperatures of 300-400 • C leads to a strong change in superconducting properties [16] and subsequent annealing of that complex in hydrogen causes an increase in the sharpness of the transition to superconducting state [17]. Finally, the chemical combination of FeSe with tetrabutyl ammonium (TBA), each molecule of which contains 36 hydrogen atoms, shifted a critical temperature in (TBA) 0.3 FeSe to the level of 50 K (from T c = 8 K for FeSe), which is currently record-breaking for bulk single crystals of this family of ICSs [18].…”
Section: Introductionmentioning
confidence: 99%
“…15 Annealing of the Fe-Te-Se compound in an oxygen atmosphere at temperatures of 300-400 °C leads to a strong changes in superconducting properties 16 and subsequent annealing of this compound in hydrogen causes an increase in the steepness of the superconducting transition. 17 Recently performed x-ray structural studies of Fe-Te-Se showed 19 that air molecules change the interlayer interaction in the tetragonal phase of the Fe-Te-Se and come up with a significant effect on the structural parameters of this superconductor. Pronounced structural changes occur under the influence of diffuse penetration of hot hydrogen (at the temperature of about 200 o C) into the sample.…”
Section: Introductionmentioning
confidence: 99%
“…15 Annealing of the Fe-Te-Se compound in an oxygen atmosphere at temperatures of 300-400 °C leads to a strong changes in superconducting properties 16 and subsequent annealing of this compound in hydrogen causes an increase in the steepness of the superconducting transition. 17 Finally, the chemical combination of FeSe with tetrabutyl ammonium (TBA), each molecule of which contains 36 hydrogen atoms, shifted a critical temperature in (TBA) 0.3 FeSe to the level of 50 K (from T c = 8 K for FeSe), what is currently record-breaking for bulk single crystals of this family of ICSs. 18 Recently performed x-ray structural studies of Fe-Te-Se showed 19 that air molecules change the interlayer interaction in the tetragonal phase of the Fe-Te-Se and come up with a significant effect on the structural parameters of this superconductor.…”
Section: Introductionmentioning
confidence: 99%